2018
DOI: 10.1038/s41467-018-03668-0
|View full text |Cite
|
Sign up to set email alerts
|

Zeb1-Hdac2-eNOS circuitry identifies early cardiovascular precursors in naive mouse embryonic stem cells

Abstract: Nitric oxide (NO) synthesis is a late event during differentiation of mouse embryonic stem cells (mESC) and occurs after release from serum and leukemia inhibitory factor (LIF). Here we show that after release from pluripotency, a subpopulation of mESC, kept in the naive state by 2i/LIF, expresses endothelial nitric oxide synthase (eNOS) and endogenously synthesizes NO. This eNOS/NO-positive subpopulation (ESNO+) expresses mesendodermal markers and is more efficient in the generation of cardiovascular precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 69 publications
(128 reference statements)
0
9
0
Order By: Relevance
“…It has been recently reported that miR-200 family expression is controlled by endogenous NO allowing for the mesendodermal differentiation of mouse embryonic stem cells 51 , 52 . miR-200 family is usually down-modulated during tumour progression.…”
Section: Resultsmentioning
confidence: 99%
“…It has been recently reported that miR-200 family expression is controlled by endogenous NO allowing for the mesendodermal differentiation of mouse embryonic stem cells 51 , 52 . miR-200 family is usually down-modulated during tumour progression.…”
Section: Resultsmentioning
confidence: 99%
“…These factors induce EMT-related stem cell properties and promote tumorigenesis via PTMs ( Mani et al, 2008 ; Tam and Weinberg, 2013 ; Ye et al, 2015 ; Dai et al, 2020 ). S-nitrosylation of HDAC2 is regulated by endothelial nitric oxide synthase (eNOS) that is a crucial enzyme for NO synthesis, allowing ZEB1 re-activation ( Cencioni et al, 2018 ). During hypoxia, HDAC3 is essential for the activation of mesenchymal gene expression by the interaction with WD repeat domain 5 (WDR5) ( Wu et al, 2011 ).…”
Section: Biological Functions Of Hdacsmentioning
confidence: 99%
“…Bl_NOS transcription also reduced with HDACi treatment. NOS is essential for the generation of nitric oxide, which has important roles in pluripotency and immune responses (Beltran-Povea et al, 2015;Cencioni et al, 2018;Lee et al, 2017). Bl_NOS mRNA is expressed in multiple cell types including haemoblasts and the regeneration niche.…”
Section: Changes To Mrna Expression During Wbr Resulting From Hdacimentioning
confidence: 99%